Work preferences and work performance of CPAs employed in the Commission on Audit Region VI (2005)
The study describe the work preferences and work performance of Certified Public Accountants (CPAs) in the Commission on audit region VI (COA RO VI). It also establishes the relationship between work preference and work performance and evaluates the level of work performance among Regional Cluster Directors, audit Team Leaders and Audit Team Members. Three strata were studied involving 38 respondents selected through random sampling. From Regional Cluster director stratum, total of 3 respondents were selected; from Team Leaders stratum, 17 respondents were selected; and from Team members stratum, a total of 18 respondents were selected. The study made use of the descriptive-analytical method that identifies, describes and analyzes the general characteristics of selected CPAs in COA RO VI. The data were analyzed and presented in descriptive statistics through tubular presentation of frequency and percentage distribution and ranking. Findings of the study present a clear picture of the work preferences of the sample respondents. Preferences for finance-related work re seen to be "high". The nature of work and the work environment in the present employer are described by the sample respondents. Their preferences with regard to nature of work and work environment are seen to be in line with what the present employer offers. Findings also bring to light the satisfactory level of work performance exemplified by sample respondents. work is accomplished on time and quality reports are submitted. However, insignificant errors in work outputs are committed due to voluminous tasks and lack of manpower assistance, hence, time management is recommended. Further, job satisfaction is achieved due to factors such as salary, career opportunities, work location, working condition, co-workers, rewards and incentives and company culture and policies. Thus, findings reveal that work preference is positively correlated with work performance. The factors of work preference, i.e. job characteristics and career advancement contribute to work performance specifically the accomplishments of work outputs, the satisfaction derived from work, and work attitudes. Findings of the study further reveal that the respondent's work attitude is affected by their co-worker's characteristics and preferred work roles and relationships. Better work performance is achieved by the respondents whose co-workers have the same characteristics with him/her because they regard them as close friends. Their thoroughness to details of work is highly valued.
[Research Paper] (Master of Management). -- [Iloilo City : UPV-CM]. March 5, 2005.